2011
DOI: 10.1002/eji.201141962
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing HIV‐1‐specific CD8+ T‐cell induction by recombinant BCG in prime‐boost regimens with heterologous viral vectors

Abstract: The desire to induce HIV-1-specific responses soon after birth to prevent breast milk transmission of HIV-1 led us to propose a vaccine regimen which primes HIV-1-specific T cells using a recombinant Mycobacterium bovis bacillus Calmette-Gué rin (rBCG) vaccine. Because attenuated live bacterial vaccines are typically not sufficiently immunogenic as stand-alone vaccines, rBCG-primed T cells will likely require boost immunization(s). Here, we compared modified Danish (AERAS-401) and Pasteur lysine auxotroph (222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…The potential use of BCG as an HIV vaccine vector was explored in preclinical studies of adult and new-born BALB/c mice using the HIV-1 clade A Gag immunogen (HIVA) (Mwau et al, 2004). Priming with recombinant BCG expressing HIVA (BCG.HIVA) induced HIV-specific T cell responses which were efficiently boosted with rMVA (MVA.HIVA) (Hopkins et al, 2011a,b; Saubi et al, 2011, 2012). In further related studies, priming with BCG.HIVA and boosting with a combination vaccine expressing HIVA and the Mtb antigen 85A (mMVA.HIVA.85A) induced robust IFN-γ-producing T cells to both HIV-1 and Mtb antigens.…”
Section: Mycobacterium Bovis Bacillus Calmette-guerin (Bcg) Vaccine Vmentioning
confidence: 99%
“…The potential use of BCG as an HIV vaccine vector was explored in preclinical studies of adult and new-born BALB/c mice using the HIV-1 clade A Gag immunogen (HIVA) (Mwau et al, 2004). Priming with recombinant BCG expressing HIVA (BCG.HIVA) induced HIV-specific T cell responses which were efficiently boosted with rMVA (MVA.HIVA) (Hopkins et al, 2011a,b; Saubi et al, 2011, 2012). In further related studies, priming with BCG.HIVA and boosting with a combination vaccine expressing HIVA and the Mtb antigen 85A (mMVA.HIVA.85A) induced robust IFN-γ-producing T cells to both HIV-1 and Mtb antigens.…”
Section: Mycobacterium Bovis Bacillus Calmette-guerin (Bcg) Vaccine Vmentioning
confidence: 99%
“…Therefore, it has been proposed that novel TB vaccine candidates should aim to preserve these unique features of BCG. In fact, among the new TB vaccine candidates under development, several are based on additional attenuations of M. bovis within the existing BCG vaccine or on attenuated M. tuberculosis strains similar to the auxotroph AMtb vaccines used here (17)(18)(19)(20)(21). Recombinant BCG strains expressing HIV antigens are also in development as potential HIV vaccines and have been tested in mice (22)(23)(24) and in adult (25)(26)(27)(28)(29) and neonatal (30) macaques.…”
mentioning
confidence: 99%
“…rBCG vaccines have been shown to efficiently prime the immune response to the heterologous antigen in recombinant adenovirus, recombinant poxvirus, and protein prime-boost combinations (24,26,27,30,57,58). We (27,44,52) and others (59) have previously shown that a Gag VLP boost, used in heterologous prime-boost modality, is a (62).…”
Section: Discussionmentioning
confidence: 96%
“…Mycobacterium bovis BCG has been investigated as a live vaccine vector for a variety of human infections (20)(21)(22)(23)(24)(25), including HIV-1 infections (26)(27)(28)(29)(30). An important and attractive feature of using BCG is its long safety record as a tuberculosis (TB) vaccine, having being injected into over 3 billion people worldwide.…”
mentioning
confidence: 99%